Повоєнне відновлення економічного потенціалу туристичної галузі України на засадах міжнародного співробітництва та інновацій - Демко, Валентина Сергіївна; Demko, Valentina; Руденко, Микола Вікторович; Rudenko, Mykola (My University, 2025)
UA: Стаття присвячена дослідженню особливостей повоєнного відновлення економічного потенціалу турис тичної галузі України на засадах міжнародного співробітництва та впровадження інновацій. У роботі систе матизовано наслідки впливу воєнних дій за трьома групами – фізичні, економічні та соціально-іміджеві, що дозволило визначити пріоритетні об’єкти та процеси для першочергового відновлення туристичної галузі. Запропоновано до впровадження пріоритетні види інновацій та smart-інструментів, зокрема інтерактивні мапи безпеки, безконтактні сервіси, цифрові двійники об’єктів культурної спадщини та платформи управління дес тинаціями (DMS). На цій основі сформовано стратегічні напрями повоєнного відновлення економічного по тенціалу туристичної галузі на засадах міжнародного співробітництва та інновацій: інтеграційно-цифровий, інвестиційно-безпековий, продуктовий та гуманітарно-технологічний, реалізація яких забезпечить інтеграцію України у світовий туристичний простір. /// EN: The article is devoted to the study of the features of the post-war recovery of the economic potential of Ukraine's tourism industry based on international cooperation and the introduction of innovations. The necessity of combining external partnership mechanisms with internal technological modernization is substantiated. Purpose. The purpose of the study is to substantiate strategic directions for the post-war recovery of the economic potential of the tourism industry of Ukraine through the development of effective mechanisms of international cooperation and the introduction of innovations and smart tourism technologies. Results. Priority types of innovations and smart tools for the domestic tourism sector are proposed, including interactive safety maps, contactless service technologies, digital twins of cultural heritage sites, and destination management systems (DMS). Strategic directions for the restoration of the industry's economic potential are formed: integration-digital (creation of a single information space with the EU), investment-security (transparency through smart infrastructure), product (creation of transborder clusters), and humanitarian-technological (development of human capital). The mechanism of their implementation based on the interaction of the state, business, and international partners is revealed. Originality. For the first time, a list of priority innovations has been structured according to the specific needs of the post-war period (security trust, transparency). The strategic vectors of integration of the Ukrainian market into the European digital tourism space are defined.Conclusions. The proposed strategic directions allow for attracting foreign investment, ensuring the safety of travel through digital solutions, and integrating Ukraine into the global tourism market. The practical implementation of these measures will contribute to the physical reconstruction of infrastructure, the return of tourist f lows, and the formation of a positive image of Ukraine as a safe and high-tech destination.
Post-war recovery of the economic potential of the tourism industry of Ukraine based on international cooperation and innovations
Keywords: економічний потенціал; туристична галузь; повоєнне відновлення; міжнародне співробіт ництво; інновації; smart-туризм; цифрова інтеграція; інвестиційна безпека; транскордонні кластери; economic potential; tourism industry; post-war recovery; international cooperation; innovations; smart tourism; digital integration; investment security; transborder clusters